Penerapan Model Cooperative Learning Berbasis HOTS dalam Meningkatkan Hasil Belajar Matematika di MI Negeri 2 Sleman - Ummu Aiman (Jurnal Pendidikan Madrasah, 2020)
This research aims to describe the application of hots-based cooperative learning models in improving mathematics learning outcomes in the smallest multiples and largest federal factors. This research uses a method of action research. The subject of the study was students of grade 4-C MI Negeri 2 Sleman in the first semester of the 2019/2020 school year. The results showed an increase in cycle 1 of 34.3%, and a 75% increase in cycle 2. Increased cycle 1 to cycle 2 by 75%. High-level cooperative learning based thinking skills can improve learning outcomes in the smallest multiples of fellowship and the largest communion factor.